Microstructural characteristics of a high-chromium cast iron hard-facing alloy - Faras, Teresa; Koenig, Benjamin; Meyer, Paul P.; Diop, Ibra (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
Hard-facing alloys increase the service life of components exposed to abrasive, erosive, or metal-to-metal wear conditions. Hard-facing is a metalworking process in which layers of a harder material are arc-welded onto a base metal. In particular, high-chromium hard-face weld deposit layers form a strong metallurgical bond with the substrate steel plate, enhancing the resistance to abrasive loadings. Metallurgical and microstructural analysis is conducted to improve the performance of such bi-layered metal structures. The discussion of an HC-O hard-face alloy deposited on S235 steel substrate plates is presented here, focusing on the characterization of the coating microstructure. The study establishes the relationship among the chemical composition, ‘as-clad’ microstructure, and hardness properties of the investigated high chromium Fe – 27 wt.% Cr – 5 wt.% C hard-facing alloy.